2022
DOI: 10.18549/pharmpract.2022.3.2721
|View full text |Cite
|
Sign up to set email alerts
|

Using laboratory parameters as predictors for the severity and mortality of COVID-19 in hospitalized patients

Abstract: Objective:The aim of this study was to explore association of initial laboratory parameters of hospitalized patients with COVID-19, with the severity and death incident. Methods: In this retrospective study, patients were classified based on mortality outcome (survivor and non-survivor) and disease severity (non-severe, severe, and critical). The initial laboratory data (within the first two days of hospital admission) were compared between these categories. Results: Of 362 COVID-19 patients hospitalized betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Multiple studies conducted on hospitalized COVID-19 patients have revealed a median age ranging between 49 and 56 years [ 3 , 7 , 8 ]. Additionally, older age has been associated with increased mortality rates [ 2 , 6 , 33 , 34 ].…”
Section: Risk Factors For Covid-19-associated Hospitalizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies conducted on hospitalized COVID-19 patients have revealed a median age ranging between 49 and 56 years [ 3 , 7 , 8 ]. Additionally, older age has been associated with increased mortality rates [ 2 , 6 , 33 , 34 ].…”
Section: Risk Factors For Covid-19-associated Hospitalizationmentioning
confidence: 99%
“…A recent retrospective study conducted in Jordan aimed to investigate the correlation between the initial laboratory parameters of hospitalized COVID-19 patients and the incidence of severity and mortality [ 6 ]. A significant statistical correlation was observed between exceeding certain laboratory parameters’ cut-off values and the severity or mortality of the condition.…”
Section: Laboratory Findings Of Covid-19 Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, socioeconomic status, diet, lifestyle, geographical differences, ethnicity, exposed viral load, day of initiation of treatment, and quality of health care have all been reported to influence individual outcomes. Furthermore, higher CRP and radiography findings at admission are associated with COVID-19 pneumonia, intensive care unit admission, and death [8][9][10][11][12].…”
Section: Covid-19 (Coronavirus Diseasementioning
confidence: 99%